PENGARUH PERILAKU INTERPERSONAL GURU TERHADAP MINAT BELAJAR MATEMATIKA SISWA KELAS X SMA ANGKASA 1 JAKARTA - Suryaratri, Ratna Dyah; Putra, Helmy (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2018)
This research aims to investigate the influence of interpersonal behavior of teacher on learning interest of Angkasa 1 Senior High School Students in 10th grade. The research method is quantitative using the Likert Scale. Thereby, researchers used the instruments, that have been adapted, the Interpersonal Behavior of Teacher. The literatures used are â€œQuestionnaire on Teacher Interactionâ€ which was written by Wubbels, Creton, and Holvast and modified/edited by Maulana, and â€œMinat Belajar Matematikaâ€ which was written by Fahrul Usman and Fitriani. There are totally 100 Angkasa 1 Senior High Schoolâ€™s students in the 10th grade between the ages of 15 and 17 as the samples of this research, which are collected by using the sampling insidental as a method. The method of data processing used for the hypothesis is regression analysis. The result is impressive, the â€˜higherâ€™ interpersonal behavior the teacher shows, the more learning interest on Mathematics the students have. After all, it shows statistically that the learning interest on mathematics is 26% influenced by the interpersonal behavior of teacher and the rest 74% by another factors.